(untitled) (Journal of the College of Basic Education, 2023)
The poem is a dialectical relationship and an effective synergy between different rhythmic and linguistic levels.and pictorial within a homogeneous composition that enters the inner world of its creator, so it forms to produce a phenomenon ora visual formation that reveals a vision of the external world, and among the manifestations of thatAntithesis" is a term that we will establish after a while, revealing the creator’s adventure in artistic creation.In an attempt to shed critical light on the manifestation of the double mental feelings thatIt is full of contradictions, and the most dangerous driver in the creativity of any artistic phenomenon is the power of emotional glow.who undermines what is perspective and establishes new relationships according to the poet’s vision within the framework ofHis use of the senses is identified with the feelings and the imagination contributes to the breaking down of the objective fencesAnd opening it towards a broader and more distant sky, the poetic image soon acquires a generalization that calls forInterpretation is based on keys that the creator spreads in his text, but walking in the dead end of imagination hasIt leads to loss and hallucinations if it escapes from the control of the mind and is liberated from its chains, which is what canReceiving it through a language whose strings are difficult to catch, and this transcendental feature that does not extend its roots “throughContradictory elements as a way to confirm the language of its suggestive-semantic totality within the framework of a negative elementIt is represented in his rejection of the idea of contradiction inherent in the poetic language” (1).Hence, the poetic language sought to transcend prosaic neutrality to say everything other thanCreating new relationships between words, and based on that, the poetic image is a spaceLinguistically, it is not satisfied with standing in front of rigid sensory templates, but it goes beyond it to seizing the noise of meanings.the hidden in all of its contrasting diodes. It has become clear with regard to the creative process inPoetic composition and formation View the text as a dynamic and complementary unit that involvescomponents melting into each other, the reception does not cut through the artistic construction of the text away from theThe material is to break up the work into parts, but it takes it in its literary context, and the context is the path of the creator.In thinking, his genius emerges, and it is a self-mould that combined the formulation of innate self-energy and effort.